Inline mach zender interferometer (IMZI) based sensors for humidity and biochemical concentration measurements / Asiah Lokman - Asiah, Lokman (2016)
Compact in-line fiber optic core cladding mode interferometers (CCMIs) have attracted much interest in recent years for various chemical, physical, and biological sensing applications. The working principle of CCMIs involves a mechanism to realize coupling and re-coupling between modes of the fiber core and fiber cladding. The core mode is guided by the core–cladding interface of the fiber while the cladding mode is guided by the cladding-ambience interface. Due to the optical phase difference (OPD) between the core and cladding modes, the CCMI could be used to measure various environmental parameters related to the ambience. This dissertation is concerned with the development of a simple and low cost fiber optics sensor based on interferometry modulated In-line Mach Zenhder Interferometer (IMZI). The proposed MZI structure is used to detect changes in relative humidity and various biochemical concentrations in distilled water. First, two main sensing methods are investigated; intensity modulation and interferometric technique are evaluated for RH measurements. A mixture of HEC and PVDF is used as a coating material for the tapered fiber. Then, the performance of the various sensors is investigated and compared. Next, a new sensor which is a dumbbell-shaped inline MZI is developed using an arcing process of a fusion splicer .The sensor probe consists of two bulges separated by a tapered waist that generates a good reflected interference spectrum.Lastly, Zink Oxide (ZnO) nanowires structure is developed and used as a coating sensitive material for the IMZI sensor. ZnO was synthesized by aqueous solution of zinc nitrate hexaydrate (Zn (NO3)2.6H2O (0.01 M) and hexamethylenetetramine (HMTA; C6H12N4] (0.01 M) in deionized (DI) water. The performance of sensors with and without ZnO nanowires coating are investigated for both RH and uric acid concentration measurements. Overall, the proposed dumbbell shape MZI sensor has a high potential as it is easy to fabricate, cheap and compact.